Resident Fibroblast MKL1 Is Sufficient to Drive Pro-fibrogenic Response in Mice - Huang, Shan; Shao, Tinghui; Liu, Hong; Li, Tianfa; Gui, Xianhua; Zhao, Qianwen (Frontiers in Cell and Developmental Biology, 2022)
Fibrosis is an evolutionarily conserved pathophysiological process serving bifurcated purposes. On the one hand, fibrosis is essential for wound healing and contributes to the preservation of organ function. On the other hand, aberrant fibrogenic response may lead to tissue remodeling and precipitate organ failure. Recently lineage tracing studies have shown that resident fibroblasts are the primary mediator of fibrosis taking place in key organs such as the heart, the lungs, and the kidneys. Megakaryocytic leukemia 1 (MKL1) is transcriptional regulator involved in tissue fibrosis. Here we generated resident fibroblast conditional MKL1 knockout (CKO) mice by crossing the Mkl1f/f mice to the Col1a2-CreERT2 mice. Models of cardiac fibrosis, pulmonary fibrosis, and renal fibrosis were reproduced in the CKO mice and wild type (WT) littermates. Compared to the WT mice, the CKO mice displayed across-the-board attenuation of fibrosis in different models. Our data cement the pivotal role MKL1 plays in tissue fibrosis but point to the cellular origin from which MKL1 exerts its pro-fibrogenic effects.